Versatile Functions of Somatostatin and Somatostatin Receptors in the Gastrointestinal System - Shamsi, Bilal Haider; Chatoo, Mahanand; Xu, Xiao Kang; Xu, Xun; Chen, Xue Qun (Frontiers in Endocrinology, 2021)
Somatostatin (SST) and somatostatin receptors (SSTRs) play an important role in brain and gastrointestinal (GI) system. SST is produced in various organ and cells, and the inhibitory function of somatostatin-containing cells involves in greater diversity physiology function and pathological modifications. GI system is the largest endocrine organ for digestion and absorption, SST-endocrine cells and neurons in GI system are a critical effector to maintain homeostasis via SSTRs 1-5 and co-receptors, SST-SSTRs involve in chemo-sensory, mucus and hormone secretion, motility, inflammation response, itch and pain by autocrine, paracrine, endocrine and exoendocrine pathway. Also it is a power inhibitor for tumor cell proliferation, severe inflammation and postoperation complication, and list as a first-line anti-cancer drug in clinical practice. This mini review focuses on the current function of producing SST endocrine cells and local neurons SST-SSTRs in GI system, and discusses new development prognostic markers, phosphate-specific antibodies and molecular imaging emerged in diagnostics and therapy, and summarizes the mechanism of SST family in basic research and clinical practice. Understood of endocrine and neuroendocrine in SST-SSTRs in GI will provide an insight into advanced medicine in basic and clinical research.